Kajian Karakteristik Terhadap Probabilitas Pemilihan Moda Untuk Aktivitas Utama (Studi Kasus : Rute Graha Raya – BSD) - Ridmawan, Adhitya Dite; Kinasih, Reni Karno (P3M- Politeknik Negeri Kupang, 2024)
Transportation is the movement of people and goods from one place to another so that transportation activities generally influence the optimal movement system from one place to another. In order to travel to the place you want to go quickly and efficiently, transportation is needed to support these needs. Travelers mostly use private vehicles to travel to their destination rather than using public transportation, causing vehicle congestion on the roads. This research aims to find out what factors influence workers in choosing modes of transportation and also maximize the use of public transportation among South Tangerang workers. Data obtained from distributing questionnaires which were then processed with the help of SPSS software included Partial Correlation Tests between Variables, Simultaneous Correlation Tests between Variables, Model Fit Tests, and Binary Logistic Regression. The results of the analysis show that there are 2 variables that have a partial influence, namely Gender and Frequency of Using the Bus. So the results obtained for the male gender who always use the bus are 99.97%, and for the female gender who always use the bus it is 84.16%.